Spectrometry analysis on Cyanobacteria for heavy metals detection in aquatic environment - Wong L.S.; Voon B.W.N.; Teo S.C.; Balakrishnan A. (EM International, 2023)
aquatic environment; bioaccumulation; carotenoid; cells and cell components; chlorophyll; concentration (composition); copper; cyanobacterium; detection method; environmental monitoring; experimental study; heavy metal; lead; spectrometry; Anabaena cylindrica; Cyanobacteria